Implementation of Land Registration Policy Complete Systematic in Realizing Legal Certainty for Rights Holders in Kendal Regency - Akbar, Ahmad Faiz; Purnawan, Amin (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
This study discusses the Implementation of the Complete Systematic Land Registration Policy (PTSL) in realizing legal certainty for rights holders in Kendal Regency. PTSL aims to provide legal guarantees for land ownership rights through systematic and integrated land registration. This study uses an empirical legal approach to analyze how PTSL is implemented and the obstacles faced in Kendal Regency. The results of the study indicate that the implementation of PTSL is hampered by limited human resources, minimal budget, and low public awareness of the importance of land certification. These obstacles have the potential to hinder the achievement of PTSL goals, namely creating justice, benefits, and legal certainty for all land owners in Kendal Regency. In the analysis using the theory of legal objectives, the implementation of PTSL is expected to be able to answer the community's need for legal certainty and encourage welfare through more productive use of land assets. Using Talcott Parsons' Structural Functionalism theory, this study also found that PTSL plays an important role in maintaining social stability by strengthening integration between the government, village officials, and the community. Recommended solutions include increasing socialization to the community about the benefits of land certification, increasing budget allocations, and increasing human resource capacity to support the smooth implementation of PTSL.